Inventing languages, inventing worlds. Towards a linguistic worldview for artificial languages - Stria, Ida (Wydział Neofilologii UAM w Poznaniu, 2016)
The present book evaluates the applicability of the linguistic worldview framework to the analysis of artificial languages and presents the limitations of such an approach. The following research conclusions were formulated: 1. Artificial languages are not a homogeneous group, and their various characteristics necessitate different perspectives in the application of the framework. 2. The binary division between artificial and natural languages is disproved; a scale of naturalness/artificiality is proposed. 3. The language which may be treated as natural is undoubtedly Esperanto. 4. Any study of artificial languages within this framework needs to take into account transfer from other languages known to the respondents as well as cultural influences. The existence of a linguistic worldview typical of Esperanto and presented consistently in the following areas was proved: cultural concepts related to the Movement and stereotype of an Esperantist.
Keywords: językowy obraz świata; linguistic worldview; linguistic picture of the world; języki sztuczne; artificial languages; języki planowe; planned languages; międzynarodowe języki pomocnicze; international auxiliary languages; constructed languages; invented languages; Esperanto; naturalność; naturalness